Approaches to Detection of Distantly Related Proteins by Database Searches. (December 1996) - Cattell, K.; Koop, B.; Olafson, R.S.; Fellows, M.; Bailey, I.; Olafson, R.W.; Upton, C.
The searching of protein databases as a method of identifying newly sequenced genes is commonplace in molecular biology laboratories. However, it is a procedure that is not usually formally taught to students, and method cookbooks discuss it only briefly. This article uses a single family of highly diverged uracil-DNA glycosylases, which fall into two distinct groups, to highlight some of the difficulties associated with identification of such proteins by database searching.